Association of G12D mutation in the KRAS gene with HPV and EBV in gastrointestinal cancer tissues - Vahideh Hamidi Sofiani; Arefeh Ebrahimian Shiadeh; Alijan Tabarraei; Hadi Razavi Nikoo; Farzin Sadeghi; Ghodsieh Kamrani; Yousef Yahyapour; Abdolvahab Moradi (Journal of International Medical Research)
Objective This study aimed to explore the potential relationship between viral infections and gastrointestinal (GI) malignancies, focusing on the presence of KRAS G12D mutations. Specifically, we investigated the association of viral agents, including human papillomavirus (HPV) and Epstein–Barr virus (EBV), with KRAS G12D mutations in GI cancers to better understand their combined role in cancer development. Methods This cross-sectional study comprised 92 patients diagnosed with GI cancer and 100 healthy individuals in the control group. All samples were examined to detect the KRAS G12D gene mutation and the existence of HPV and EBV using real-time polymerase chain reaction assays. Results HPV and EBV DNA were detected in 5.4% and 51.4% of gastric cancer samples and in 7.3% and 49.1% of colorectal cancer samples, respectively. Analysis of KRAS G12D in plasma samples revealed heterozygous mutations in 54% of patients with gastric cancer and 35% of patients with colorectal tumors. Among EBV-positive colorectal cancer samples, 1.8% were wild-type, while 47.2% exhibited heterozygous mutations. Among HPV-positive colorectal cancer patients, 1.8% exhibited wild-type KRAS, 5.4% had heterozygous mutations, and 3.2% had homozygous mutations. Conclusion This study detected a significant correlation between the presence of viral agents and KRAS G12D mutations.